2020
DOI: 10.1002/pol.20190099
|View full text |Cite
|
Sign up to set email alerts
|

Ion transport mechanisms in salt‐doped polymerized zwitterionic electrolytes

Abstract: Polyzwitterions (polyZIs), macromolecules with repeating ampholytic monomers, are a novel class of materials with attractive properties for battery electrolytes. In this study, we probe the ion transport characteristics and underlying mechanisms in two salt‐doped (Li+‐TFSI−) polyZIs of similar composition with contrasting zwitterion (ZI) ionic organization: pendant monomers organized via backbone‐anion‐cation (B‐ZI−‐ZI+, Motif B) and backbone‐cation‐anion (B‐ZI+‐ZI−, Motif C). Within both Motifs B and C, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 79 publications
2
24
0
Order By: Relevance
“…For mixtures containing ILs and lithium ions, Borodin and coworkers 87 found that the [Li] + transport is correlated to ion pair lifetime (or “residence time”) of the [Li] + − [Anion] − interaction, and that longer lifetimes lead to slower lithium diffusion. Similarly, for mixtures of PEO with ILs and Li‐salts, Mogurampelly and Ganesan 75 found that while the diffusion mechanism of the [Cation] + is correlated with the [Cation] + − [Anion] − lifetime, the [Li] + diffusion is more correlated to the oligomer segmental dynamics, agreeing with the structural organization of the system, in which the oligomer chains coordinate strongly to the lithium ions.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…For mixtures containing ILs and lithium ions, Borodin and coworkers 87 found that the [Li] + transport is correlated to ion pair lifetime (or “residence time”) of the [Li] + − [Anion] − interaction, and that longer lifetimes lead to slower lithium diffusion. Similarly, for mixtures of PEO with ILs and Li‐salts, Mogurampelly and Ganesan 75 found that while the diffusion mechanism of the [Cation] + is correlated with the [Cation] + − [Anion] − lifetime, the [Li] + diffusion is more correlated to the oligomer segmental dynamics, agreeing with the structural organization of the system, in which the oligomer chains coordinate strongly to the lithium ions.…”
Section: Resultsmentioning
confidence: 67%
“…In ternary mixtures such as IL/Polymer/[Li] + , there is a strong interaction between the lithium ion and the polymer chains that leads to the decoupling of the IL anion –[Li] + interaction and consequently to changes in the ionic diffusion mechanisms as compared to the neat IL with salt. In a series of papers, 71–76 Ganesan and coworkers have shown this effect for different mixtures containing ILs and polymers. For a ternary system containing PEO/IL/[Li] + (IL = 1‐butyl‐3‐methylimidazolium hexafluorophosphate), 71 the authors observed that the increase in IL content enhances the ionic mobilities due to the weakening in the IL anion –[Li] + interaction.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The restrained electrostatic potential (RESP) was post‐processed through Multiwfn package 68,69 . The resulting partial charges were further scaled down by a factor of 0.8 for obtaining better agreement of dynamical properties with respect to experiments 47–49,70,71 …”
Section: Methodsmentioning
confidence: 99%
“…In a series of studies, we have used atomistic simulations to examine the mechanisms underlying ionic conductivity in a variety of polyIL based systems 33,43–49 . In this context, our most recent study considered the ion mobilities and transport mechanisms in salt‐doped polyILs 50 .…”
Section: Introductionmentioning
confidence: 99%